Strategies to Enhance Inpatients’ Revisit Intention through the Blue Ocean Strategy and Customer Satisfaction Index - A. Dwi Hermin Alfian; Yusriani Yusriani; Yuliati Yuliati; Nur Ulmy Mahmud; Muh. Khidri Alwi (Journal La Medihealtico, 2026)
Patients’ revisit intention represents a crucial indicator of hospital service sustainability and is strongly influenced by service quality and patient satisfaction. Amid increasingly intense competition among healthcare providers, hospitals are required to develop innovative strategies that emphasize value creation and patient experience. The Blue Ocean Strategy approach, combined with patient satisfaction measurement using the Customer Satisfaction Index (CSI), offers a strategic alternative for enhancing hospital competitiveness. This study aimed to analyze the relationship between the implementation of the Blue Ocean Strategy and the Customer Satisfaction Index with patient satisfaction, as well as their association with inpatient revisit intention at Permata Hati Mother and Child Hospital, Makassar City. This study employed an analytic quantitative design with a cross-sectional approach. A total of 190 hospitalized patients were selected as respondents using purposive sampling techniques. Data were analyzed descriptively and bivariately using Pearson correlation and Chi-square tests. The results indicated that the majority of respondents were aged 30–39 years, female, and users of the National Health Insurance (BPJS Kesehatan) scheme. Bivariate analysis revealed a significant relationship between the implementation of the Blue Ocean Strategy and inpatient satisfaction (p < 0.05), as well as a significant association between the Customer Satisfaction Index and patient satisfaction (p < 0.05). Furthermore, patient satisfaction was found to be significantly associated with inpatient revisit intention at Permata Hati Mother and Child Hospital, Makassar City (p < 0.05). In conclusion, the implementation of innovative service strategies and higher levels of patient satisfaction are significantly associated with inpatients’ revisit intention.